Annual report to the Government of St. Lucia 1988 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
The documents presents a general information, a history of IICA in St. Lucia. Continuously, a summary of report and presentation of the following technical cooperation projects: 1) Support for the organization and management of technology generation and transfer in the OECS; 2) Strengthening of farmer organizations in the OECS; 3) Strengthening plant protection and quarantine capabilities in the Windward Islands and Antigua and Barbuda for the marketing of non-traditional crops. Then, the report presents short term activities: 1) OECS diversification programme; 2) Agricultural sector assessment for project identification Antiguay Barbuda and St. Vincent and the Grenadines; 3) Validation of sheep production systems - Dominica; 4) Interin management of Amblyomma variegatum eradication (Dominica, St. Lucia); 5) Improved management of inter-personal relationships St. Lucia; and, 6) A pilot study of farm incomes - Grenada. Finally, training participation, project unit/regional projects, staff and expenditure.